Meningitis caused by the varicella vaccine virus in 17 immunized children and adolescents from the United States, Europe, and Japan - Charles Grose; Daniel J. Bonthius (Wiley, 2023)
Abstract The varicella vaccination program has an excellent safety record. The vaccine virus, like its wild‐type counterpart, can enter latency and later reactivate as herpes zoster. A lesser known but serious adverse event following reactivation is varicella vaccine meningitis. We investigate that adverse event. We performed a literature search using the PubMed and Google Scholar search engines to locate all published cases of varicella vaccine meningitis. We continued the search through January 2023. We found 17 cases of varicella vaccine meningitis. The first case was published in 2003, and the last case was published in 2023. The children lived in the United States, Greece, Germany, Switzerland, and Japan. Among the 17 cases, 14 were immunocompetent; nine of the 17 were adolescents. One potential risk factor was the administration of corticosteroids three to four weeks before the onset of meningitis. Varicella vaccine meningitis is a rare but one of the more serious adverse events that occurs several years following varicella vaccination. In immunocompetent children, this complication is treatable with a single course of intravenous acyclovir after hospitalization.